The propagation of dipole solitons in highly nonlocal medium - 赵嘉胤 王奇 申明 施解龙 孔茜 葛丽娟 (Chinese physics B, 2010)
This paper studies the propagation of dipole solitons in highly nonlocal medium by using the variational method. It finds that the dipole solitons will be stable when the input power obeys a restrict value. When the incident power does not satisfy the stable conditions, the nonlocal accessible dipole solitons will undergo linear harmonic oscillation. It shows such evolution behaviours in detail.